Extremely high and elongated power output from a mechanical mediator-assisted triboelectric nanogenerator driven by the biomechanical energy. (February 2019) - Yoo, Jaewon; Yoo, Donghyeon; Lee, Seoulmin; Sim, Jae-Yoon; Hwang, Woonbong; Choi, Dongwhi; Kim, Dong Sung
Abstract: The triboelectric nanogenerator (TENG) is considered as a promising auxiliary source of power for portable and wearable devices. However, the power output from previously suggested TENGs driven with biomechanical energy has been insufficient for practical applications. This study suggests the concept of a Mechanical Mediator-Assisted TENG (MMA-TENG). The proposed MMA-TENG is constructed by adding a mechanical mediator (MM), which is based on a novel mechanical gear mechanism that transforms the input motion into a more favorable form for generation, to an existing freestanding rotational TENG (FR-TENG). The addition of the MM makes the MMA-TENG capable of generating an extremely high and elongated power output despite the kinematic limitations of biomechanical movements (low velocity of ~10 0 m/s and low frequency of ~ 10 0 Hz). Driven with a single hand grip motion, the MMA-TENG can generate energy at a frequency of up to 2500 Hz and realize a strikingly high power output of up to 26 mW at an optimal matching impedance of 2 MΩ. Also, it continues to generate energy for an elongated duration of 7 extra seconds after the hand grip input motion is stopped, thereby harvesting 96 mJ of energy from 8000 cycles in total. This amount is over 1000 times of that harvested from the FR-TENG without the MM for the same input (0.084 mJ from 7 cycles). After the investigation into the output characteristics of the MMA-TENG, the principle by which such striking output characteristics are enabled with it is intensively studied through a detailed kinetic analysis. Finally, several proof-of-concept demonstrations with the MMA-TENG including a charging of a 100 μF capacitor with an extremely high charge transfer quantity of ~300 μC for a single hand grip input, and a real-time generation of 5 V DC output with a buck-boost circuit are shown. Such outstanding characteristics of the MMA-TENG are expected to greatly widen the applicability of TENGs as a potent and practical biomechanical energy harvester to aid the powering of portable and wearable electronic devices. Graphical abstract: Highlights: A mechanical way to increase power output of triboelectric nanogenerator is proposed. A rationally designed gear mechanism enables high and elongated power output. From hand grip, high generation frequency of 2500 Hz and power of 26 mW is achieved. From a single hand grip motion, the MMA-TENG transfers 300 µC of electrical charges.